ChemInform Abstract: Phosphine‐Free Tetradentate Salicylaldimine Ligand Complexed with Palladium: First Application in Heck Reactions. Issue 12 (March 2015) - Kalhapure, Rahul S.; Govender, Thirumala; Akamanchi, Krishnacharya G.
Abstract Advantages of the introduced method are mild reaction conditions, short reaction times and low palladium loading.